Effect of phosphate - solubilizing bacteria and compost on the nutritional characteristics of the oil palm crop (Elaeis guineensis Jacq.) in Casanare, Colombia - Anamaría García; Angulo Jimena; María Mercedes Martínez; Viviana Gutiérrez (Agronomía Colombiana, 2012)
In accordance with interest to include biological practices in fertilization programs for commercially important crops, the effect of a bioinoculant application based on phosphate solubilizing bacteria along with compost was evaluated on oil palm cultivation in the nursery stage and in a definitive area. The five treatments that were evaluated included: (C) compost, (CQ) compost and chemical fertilizers 50/50, (IC) compost and inoculant, (IQ) chemical fertilizers and inoculant and (ICQ) inoculant, compost and chemical fertilizers 50/50; as a positive control it was used a plant group fertilized with traditional chemical compounds. Organic matter was added at 2% (w/w) at nursery stage and 15 kg/plant in the definitive area. Response variables includedagronomic variables were evaluated (total height, height to bifurcation, bulb diameter and number of leaves) and soil physicochemical variables (pH, oxidizable organic carbon (OOC), extractable phosphorus and total boron), measured during 8 months in the nursery area and 6 months in the definitive area. The results showed that the evaluated compost constitutes an alternative for palm fertilization in the definitive area, as source of nutrients that meet crop demand at this stage of the crop, matching the nutritional levels of the control plants (P≥0.005). Meanwhile, in the nursery area, chemical fertilization is essential to ensure the quality of the plants during the first stage of growth, since, at this stage, plants require high amount of N, which is not supplied by the compost. Finally, it was not possible to demonstrate the promoting effect of the microbial inoculant on plant growth, so it is necessary to complement this research in regard to this product